227k views
0 votes
I know the answer is -2 but I need to show my work on how I got it

I know the answer is -2 but I need to show my work on how I got it-example-1
User Gilad Gat
by
5.9k points

2 Answers

5 votes

6x + 10 = 1x

Subtract 10 from both sides

6x + 10 (-10)= 1x (-10)

6x =1x - 10

Subtract 1x from both sides

6x (-x) = 1x (-x) - 10

5x = -10

Divide both sides by 5

5x (/5) = -10 (/5)

x = -2

Hope that helps :)

User Gilad Foyer
by
5.6k points
6 votes

Answer:

-2

Explanation:

6x + 10 = 1x

Subtract 6x from both sides.

10 = -5x

------------ Divide by -5

-5

-2 = x

User Rsjaffe
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.